Some Generalized Difference Sequence Spaces Defined by a Sequence of Moduli in n-Normed Spaces - Abdullah Alotaibi; Kuldip Raj; S. A. Mohiuddine (Journal of Function Spaces)
We introduce some new generalized difference sequence spaces by means of ideal convergence, infinite matrix, and a sequence of modulus functions over n-normed spaces. We also make an effort to study several properties relevant to topological, algebraic, and inclusion relations between these spaces.